PENGARUH PEMBERIAN LARUTAN DAUN BINAHONG DALAM AIR MINUM TERHADAP PERFORMA AYAM BROILER FASE AWAL (The Effect of Administration of Binahong Leaf Solution in Drinking Water on The Performance of Early Phase Broiler Chicken) - Venansius M M. Jerahu; Ni Putu F. Suryatni; Herowati Titi Pangestuti; Herayanti P. Nastiti (JURNAL NUKLEUS PETERNAKAN, 2023)
The purpose of this study was to determine the effect of giving binahong leaf solution on the performance of early-phase broilers. The material used was 96 DOC Strain CP 707 broiler chickens produced by PT Charoen Pokphan Indonesia. This study used a completely randomized design (CRD) with four treatments and six replications. The treatments tried were: R0: Drinking water without binahong leaf solution, R1: Drinking water containing 20 ml of binahong leaf solution per liter of water, R2: Drinking water containing 30 ml of binahong leaf solution per liter of water, R3: Drinking water containing 40 ml of solution binahong leaves per liter of water. Parameters measured were daily body weight gain, feed intake, feed conversion ratio and water intake. The results of the statistical analysis showed that the treatment had no significant effect (P>0.05) on feed intake, daily body weight gain, feed conversion ratio and drinking water intake. The conclusion of this study was that the administration of binahong leaf solution with levels of 0, 20, 30 and 40 ml/l drinking water gave the same effect on the performance of early-phase broilers.